PERSEPSI MAHASISWA KOTA KUPANG TERHADAP PENERAPAN CBDC DI INDONESIA - Andel Martinus; Maria Indriyani Hewe Tiwu; Novi Theresia Kiak (Universitas Udayana, 2024)
This study aims to determine the effect of perceived benefits, convenience and security on the application of central bank digital currency from the perspective of students in Kupang city. This research uses a quantitative approach, namely analyzing data that processes data from respondent survey results. In determining the sample using Simple Random Sampling and the sample used in this study were 100 students in Kupang City as primary data. Data collection using questionnaires distributed to students studying in Kupang city. The data analysis technique used in this research is multiple linear regression analysis, T test and F test. The results of this study indicate that perceived benefits, convenience and security have a significant effect on the application of CBDC. Keywords: Digital Rupiah, Central Bank Digital Currency, perceived usefulness, perceived convenience, perceived security